(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2024)
This study examines the influence of performance and technological readiness on the operational effectiveness of police officers in the Kenya Police Service, with a focus on Machakos County. Employing a descriptive survey design and a stratified random sampling of 203 police constables and four station commanders across twelve stations, the research integrates both quantitative and qualitative data to evaluate the intersection of technology adoption and institutional performance. Findings indicate a strong positive correlation between technological preparedness and police performance, emphasizing that enhanced administrative capacity, especially in digital tools and support systems plays a critical role in improving law enforcement effectiveness. However, the study also reveals a significant gap in the implementation of such capacity improvements at the station level, leading to underperformance among frontline officers. These insights highlight the importance of targeted reforms in human resource development, workload management, and technological integration to strengthen the overall governance and service delivery of public security institutions. Situated within a broader discourse on public sector modernization in developing contexts, the study contributes to policy discussions on administrative reform, digital governance, and institutional performance.